2013
DOI: 10.1159/000355164
|View full text |Cite
|
Sign up to set email alerts
|

Low Levels of Low-Density Lipoprotein Cholesterol: A Negative Predictor of Survival in Elderly Patients with Advanced Heart Failure

Abstract: Objectives: There are conflicting reports on the role of cholesterol as an adverse prognostic predictor in patients with heart failure (HF). This study aimed to examine the impact of low levels of low-density lipoprotein cholesterol (LDL-c) on cardiac mortality in a cohort of elderly patients with moderate and severe HF. Methods: Chronic HF patients from the HF Unit at the Tel-Aviv Medical Center (n = 212, 77% males) with an average NYHA classification of 2.8, a mean age of 76.9 ± 7.3 years (range 66-91) and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 26 publications
4
17
0
2
Order By: Relevance
“…However, whether these or other mechanisms mediate the low LDL phenotype to be proatherogenic warrants further investigation. Very low LDL concentrations, along with lower HDL concentrations and triglyceride levels, have also been linked to higher mortality in patients with moderate‐to‐severe heart failure . Whether this phenomenon is due to an increase in atherosclerosis, consistent with our findings, or is a consequence of malnutrition and/or the cachectic hypermetabolic state of advanced heart failure is unclear.…”
Section: Discussionsupporting
confidence: 82%
“…However, whether these or other mechanisms mediate the low LDL phenotype to be proatherogenic warrants further investigation. Very low LDL concentrations, along with lower HDL concentrations and triglyceride levels, have also been linked to higher mortality in patients with moderate‐to‐severe heart failure . Whether this phenomenon is due to an increase in atherosclerosis, consistent with our findings, or is a consequence of malnutrition and/or the cachectic hypermetabolic state of advanced heart failure is unclear.…”
Section: Discussionsupporting
confidence: 82%
“…A number of studies have shown that MPV is associated with cardiovascular risk factors and is a prognosticator of cerebrovascular events. It has been demonstrated recently that a low LDL-cholesterol level is a poor prognosticator in patients with chronic HF 29. This is the case in our study population where the median ejection fraction was 31%, representing severely impaired LV function.…”
Section: Discussionsupporting
confidence: 49%
“…This finding on the J-curve relationship between LDL-C levels and outcomes is important because it indicates that lower LDL-C levels under statin treatments do not necessarily relate to better outcomes. This finding is consistent with previous studies reporting that a low LDL-C level was a negative predictor of survival in HF patients 49,50 and a recent population-based observational cohort study with 31619 IHD patients showing no decrease in cardiac events from lowering LDL-C level to <70 mg/dL compared with LDL-C of 70 to 100 mg/dL. 20 Although it is speculative, the lack of statin benefits in patients with low LDL-C levels could be explained, at least in part, by the poor outcomes of patients with cardiac cachexia accompanied by progressive involuntary weight loss and lower LDL-C. 51,52 Indeed, several studies have reported that lower BMI was significantly associated with poor prognosis in HF patients, whereas obese patients have rather better outcomes, known as the "obesity paradox."…”
Section: Lower-intensity Statinsupporting
confidence: 93%